NEW MODEL FOR AUTOMATIC COMPENSATION OF THE REACTIVE COMPONENT OF THE CONSUMED CURRENT OF ASYNCHRONOUS MOTORS (Conferencea, 2023)
The article considers a model for automatic compensation of the reactive component of the consumed current of asynchronous motors operating at powers lower than the nominal values. Automated control system designed for individual compensation of the reactive component of power consumption connected directly to the asynchronous motors of machine tools